Cassava Pulp Hydrolysis under Microwave Irradiation with Oxalic Acid Catalyst for Ethanol Production - Hermiati, Euis; Tsubaki, Shuntaro; Azuma, Jun-ichi (Journal of Mathematical and Fundamental Sciences, 2014)
Microwave irradiation is an alternative method of starch hydrolysis that offers a rapid process. The aim of this research was to improve microwave-assisted hydrolysis of cassava pulp by using oxalic acid as a catalyst. Suspension of cassava pulp in 0.5% oxalic acid (1 g/20 mL) was subjected to microwave irradiation at 140-230 °C for 5 minutes, with 4 minutes of pre-heating. One gram of fractured activated carbon made of coconut shell was added into a number of suspensions that were subjected to the same conditions of microwave irradiation. The soluble fraction of the hydrolysates was analyzed for its total soluble solids, malto-oligomer distribution, glucose content, pH value, and formation of brown compounds. The effects of the combined severity parameter at a substrate concentration of 5-12.5% on the glucose yield were also evaluated. The highest glucose yield (78% of dry matter) was obtained after hydrolysis at 180 °C without activated carbon addition. Heating above 180 °C reduced the glucose yield and increased the pH and the formation of brown compounds. The use of activated carbon in microwave-assisted acid hydrolysis of cassava pulp reduced the glucose yield, but suppressed the formation of brown compounds. The highest glucose yield (70-80% of dry matter) was attained at a severity parameter of 1.3-1.5.